2019
DOI: 10.1177/2277975219857411
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Health in Rural India: Enhancing Job Performance of Lay Health Care Activists

Abstract: The health of people in a nation is a potential indicator of its development. Over and above that, the job performance of people involved in the delivery and facilitation of health care services within a nation reflects the actual health conditions in it. In developing countries, where a large chunk of the population lives in rural areas, the job performance of grass-roots health care workers gains significant importance in order to ensure effective and efficient delivery of health care services to the masses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Future studies could also look at lay healthcare workers and community healthcare workers in emerging economies. 33,34 The strengths of this study are that the mediation analysis conducted are done with the very latest mediation analysis methodology, 30 and so our results are trustworthy and up to date. The primary implication from our study is that nurse managers and healthcare leaders should focus on creating principled and benevolent ethical climates in order to increase trust in their organizations and/or to reduce turnover intention.…”
Section: Discussionmentioning
confidence: 87%
“…Future studies could also look at lay healthcare workers and community healthcare workers in emerging economies. 33,34 The strengths of this study are that the mediation analysis conducted are done with the very latest mediation analysis methodology, 30 and so our results are trustworthy and up to date. The primary implication from our study is that nurse managers and healthcare leaders should focus on creating principled and benevolent ethical climates in order to increase trust in their organizations and/or to reduce turnover intention.…”
Section: Discussionmentioning
confidence: 87%
“…While it tried to explore the mechanism of this relationship, other outcomes still remain unexplored. In the future, scholars can focus on other important outcomes, such as performance and life satisfaction in different contexts, such as public health (Pandey et al, 2020), to present a comprehensive snapshot of how safety coaching can have a wide-ranging impact on other work as well as non-work outcomes. Furthermore, all the measures used in this study are self-reported.…”
Section: Safety Coaching and Work Engagementmentioning
confidence: 99%
“…Inability to adhere to gendered roles as well as infrequent pay (Ramesh 2020) instigate families to encourage the ASHAs to quit their work, further devaluing their contributions. ASHA workers have, in this way, come to embody an "inner role conflict" when their profession as healthcare worker conflicts with their social identities (Pandey et al 2019).…”
Section: Embodied Management Of Covid-19 In Indiamentioning
confidence: 99%